Characterization by Symmetry of Solutions of a Nonlinear Subelliptic Equation on the Heisenberg Group (Journal of Mathematical Study, 2017)
In this paper we prove that two calculus lemmas, which are used in themethod of moving sphere for classifying certain constant curvature equation, also holdon Heisenberg group $\mathbb{H}^n$.
Keywords: Classification; moving sphere method; Heisenberg group.